PROBLEMS OF TERMINOLOGY IN THE TRANSLATION BUSINESS - Gulden Maratovna Жетепова (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
The article deseribes problems of terminology in thanslation